Interleukin-35 Inhibits TNF-α-Induced Osteoclastogenesis and Promotes Apoptosis via Shifting the Activation From TNF Receptor-Associated Death Domain (TRADD)–TRAF2 to TRADD–Fas-Associated Death Domain by JAK1/STAT1 - Peng, Mingzheng; Wang, Yanguo; Qiang, Lei; Xu, Yan; Li, Cuidi; Li, Tao; Zhou, Xiaojun; Xiao, Ming; Wang, Jinwu (Frontiers in Immunology, 2018)
Over-activated osteoclasts derived from myeloid or peripheral blood monocytes by inflammatory cytokines results in osteoporosis, osteoarthritis, and other bone erosion-related diseases. Interleukin 35 (IL-35) is a novel anti-inflammatory and immunosuppressive factor. This study investigated the effect of IL-35 on TNF-α-induced osteoclastogenesis. In the presence of IL-35, this process was detected by Tartrate-Resistant Acid Phosphatase (TRAP) staining, F-actin staining, and bone resorption assays. The effects of IL-35 on TNF-α-induced apoptosis were demonstrated by TUNEL staining, cell viability assays, and flow cytometry. Moreover, a microarray was performed to detect the effect of IL-35 on TNF-α-activated phosphatase kinase. The effect of IL-35 on the TNF-α-mediated activation of NF-κB, MAPK, TRAF2, RIP1, Fas-associated death domain (FADD), and caspase3 was further investigated. In addition, a murine calvarial osteolysis model was established via the subcutaneous injection of TNF-α onto the calvaria, and histological analysis was subsequently performed. As a result, IL-35 inhibited TNF-α-induced osteoclast formation and bone resorption in vitro and osteolysis calvaria in vivo. NFATc1, c-fos, and TRAP were downregulated by IL-35 through the inhibition of NF-κB and MAPK, during which JAK1/STAT1 was activated. Moreover, based on TUNEL staining and flow cytometry, IL-35 was shown to enhance TNF-α-induced osteoclast apoptosis. Meanwhile, FADD and cleaved-caspase 3 were increased in cells treated with TNF-α and IL-35, whereas the DNA-binding activity of NF-κB was increased in TNF-α-treated cells, but was decreased in cells treated with both TNF-α and IL-35. In conclusion, IL-35 inhibits TNF-α-induced osteoclastogenesis and promotes apoptosis by activating JAK1/STAT1 and shifting activation from TNF receptor-associated death domain (TRADD)-TRAF2/RIP1-NF-κB to TRADD-FADD-caspase 3 signaling.